2022
DOI: 10.1186/s12864-022-08310-4
|View full text |Cite
|
Sign up to set email alerts
|

AMPlify: attentive deep learning model for discovery of novel antimicrobial peptides effective against WHO priority pathogens

Abstract: Background Antibiotic resistance is a growing global health concern prompting researchers to seek alternatives to conventional antibiotics. Antimicrobial peptides (AMPs) are attracting attention again as therapeutic agents with promising utility in this domain, and using in silico methods to discover novel AMPs is a strategy that is gaining interest. Such methods can sift through large volumes of candidate sequences and reduce lab screening costs. Results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 54 publications
0
74
0
Order By: Relevance
“…In line with these results, few reports have been published describing this rare antimicrobial activity, making Tp0451a_C a new addition to this select group of S. pyogenes -targeting AMPs. Furthermore, the anti- S. pyogenes activity of Tp0451a_C was found to be generally comparable ( Cogen et al, 2010 ; Uhlmann et al, 2016 ; Ma et al, 2020 ) or more potent ( Sornwatana et al, 2018 ; Li et al, 2022 ) than known AMPs from other organisms. The relatively small number of AMPs that show activity against S. pyogenes is attributed to the expression of several proteins involved in AMP resistance, including the streptococcal cysteine protease SpeB ( Schmidtchen et al, 2002 ) which is involved in the proteolytic degradation and inactivation of AMPs, the M1 protein, streptokinase, and the streptococcal inhibitor of complement, the latter three of which are involved in resistance against defensins and/or LL-37 ( Frick et al, 2003 ; Lauth et al, 2009 ; Hollands et al, 2012 ).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In line with these results, few reports have been published describing this rare antimicrobial activity, making Tp0451a_C a new addition to this select group of S. pyogenes -targeting AMPs. Furthermore, the anti- S. pyogenes activity of Tp0451a_C was found to be generally comparable ( Cogen et al, 2010 ; Uhlmann et al, 2016 ; Ma et al, 2020 ) or more potent ( Sornwatana et al, 2018 ; Li et al, 2022 ) than known AMPs from other organisms. The relatively small number of AMPs that show activity against S. pyogenes is attributed to the expression of several proteins involved in AMP resistance, including the streptococcal cysteine protease SpeB ( Schmidtchen et al, 2002 ) which is involved in the proteolytic degradation and inactivation of AMPs, the M1 protein, streptokinase, and the streptococcal inhibitor of complement, the latter three of which are involved in resistance against defensins and/or LL-37 ( Frick et al, 2003 ; Lauth et al, 2009 ; Hollands et al, 2012 ).…”
Section: Discussionmentioning
confidence: 95%
“…It is also likely that T. pallidum encounters pathogenic / uropathogenic strains of E. coli during infection. Although these strains were not tested in our antimicrobial susceptibility assays, previous studies have shown that AMPs from other organisms exhibit similar levels of antimicrobial activity against both non-pathogenic and pathogenic / uropathogenic E. coli strains ( Fedders et al, 2010 ; Aghazadeh et al, 2019 ; Mardirossian et al, 2019 ; Moazzezy et al, 2020 ; Li et al, 2022 ; Lin et al, 2022 ). Tp0749_C also exhibited antimicrobial activity against the Gram-negative bacterium, P. aeruginosa .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is predicted that DDIP1 is effective against a variety of mutated viral strains, since it may damage viral envelopes to prevent infection in a similar manner to disrupt bacterial membranes. Our discovery of novel antiviral peptides may be further accelerated by applying the machine learning/artificial intelligence algorithms [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] that enable the prediction of both the antiviral activity and toxicity of peptides with the accumulation of experimental data of AMPs.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, there has so far been a lack of success in translating AMP-based therapy to clinical use, due to challenges such as complex structure-activity relationship (SAR), drug toxicity, instability in host and infective environment, and low financial incentives 11,12 . Owing to the complex SAR and the costly and timeconsuming process of wet-lab experiments associated with AMP investigations, many researchers have proposed computational approaches, including molecular dynamics (MD) simulations and machine learning (ML) algorithms, to accelerate the discovery and development of potential AMPs for clinical use [13][14][15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%